Nonsynchronous Data and the Covariance‐Factor Structure of Returns - SHANKEN, JAY (Journal of Finance, 1987)
ABSTRACT Evidence is presented that indicates that the standard estimator of the covariance matrix of daily returns provides a distorted view of the true covariance‐factor structure. An alternative estimator, based on a model of the price‐adjustment delay process, reveals roughly twice as much covariation in individual security returns. The number of factors identified also appears to increase when this estimator is employed. Since the linear space spanned by the estimated factor‐loading vectors is quite sensitive to the estimator used, it is important that the consistent estimator be considered in the usual two‐stage empirical investigations of the APT.